ANALYSIS OF VARIANCE OF PERFORMANCE INDICATORS OF COMPANIES THAT PASSED BY BUSINESS COMBINATION TRANSACTIONS - Macohon, Edson Roberto; Moreira Zittei, Marcus Vinícius; Klann, Roberto Carlos (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
The objective of this research is to analyze the variance of performance indicators of 47 companies listed on the BM&FBOVESPA that have gone through business combination operations in 2010. From a quantitative approach, the study is characterized as descriptive, it is conducted through documentary analysis using ANOVA. The analysis factors are the year, from 2008 to 2015 and Sector, which covers seven sub-divisions. The ANOVA analysis does not indicate that there are statistically significant differences between the different levels of the Year factor. The variable ROA showed variance in relation to the sector factor. Thus, the significant variability of ROA index is not correlated to the M&A process. It is concluded that the statistically significant changes in the period of analysis cannot be correlated to business combination transactions (M&A).